은닉 통신을 위한 다중안테나 전이중 릴레이 기법 - 류종열(Jong Yeol Ryu); 이정훈(Jung Hoon Lee) (한국정보통신학회논문지, 2024)
본 논문에서는 은닉 통신 시스템에서 다중안테나 전이중(full-duplex) decode-and-forward(DF) 릴레이 기법을 고려한다. 먼저 전이중 DF 릴레이를 활용한 시스템에서 은닉 통신을 달성할 수 있는 은닉 조건을 유도하고, 다음으로 유도된 은닉 통신 조건을 만족하면서 수신단의 은닉 전송률을 최대화하는 릴레이 빔형성(beamforming) 기법을 설계한다. 구체적으로 수신단의 은닉 전송률을 최대화하는 릴레이 빔형성 벡터와 은닉 조건을 최소화하는 릴레이 빔형성 벡터를 각각 독립적으로 설계하고, 다음으로 은닉 조건 충족과 은닉 전송률 최대화를 달성하기 위해 설계된 두 종류의 빔형성 벡터를 선형조합해서 최종 빔형성 벡터를 설계한다. 시뮬레이션 결과를 통해 제안한 다중안테나 전이중 DF 릴레이 빔형성 기법이 기존 기법의 은닉 전송률을 개선할 수 있음을 보인다. In this paper, we consider a full-duplex decode-and-forward(DF) relaying with multiple antennas for a covert communication system. We first derive the covert communication constraint that achieves the successful covert communication for the covert communication system with full-duplex DF relay. Then, we design the relay beamforming vector in order to maximize the covert rate of the destination subject to the covertness requirement of the system. Specifically, we first design the relay beamforming vector that maximizes the covert rate of the destination and relay beamforming vector that minimizes the covertness requirement of the system, independently. Then, we finally design the relay beamforming vector as a linear combination of the designed two type of beamforming vectors to achieve both covert rate maximization and covertness requirement. In the simulation results, we show that the proposed full-duplex DF relay beamforming technique improve the covert rate comparing to the existing schemes. KCI Citation Count: 0